2015
DOI: 10.3126/jpn.v5i10.15641
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of cervical smears for detection of precancerous lesions

Abstract: Background:  Diseases of the cervix are common in women. Detection of neoplastic lesions is of prime importance in the evaluation of cervical smears although their frequency is less than the non-neoplastic conditions. Reactive and inflammatory conditions, however, may mimic or obscure the dysplastic changes. The aim of this study was to evaluate the frequencies of various inflammatory, reactive and neoplastic   lesions in the cervical smears.Materials and Methods: This was a retrospective study of 150 cases of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
1
1
Order By: Relevance
“…In our study, 3.6% of sample ware excluded from study due to sample inadequacy or being unsatisfactory which was lower than reported by 16,17,19,22,23 Bacterial vaginosis (1.9%) was the commonest organism isolated in our study which is same as reported by other studies done in Nepal and India. The percentage reported in these study vary from 3.3% to 7.6%.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…In our study, 3.6% of sample ware excluded from study due to sample inadequacy or being unsatisfactory which was lower than reported by 16,17,19,22,23 Bacterial vaginosis (1.9%) was the commonest organism isolated in our study which is same as reported by other studies done in Nepal and India. The percentage reported in these study vary from 3.3% to 7.6%.…”
Section: Discussioncontrasting
confidence: 42%
“…The percentage reported in these study vary from 3.3% to 7.6%. 16,21,22 Trichomonas was the next common organism reported on this study. The reason for lower percentage of infections in this study could be due to the fact that all women with obvious sign of infection during Pap smear were treated for their infection prior to taking sample.…”
Section: Discussionmentioning
confidence: 99%